The Academician V. D. Belyakov - the Founder of the Domestic Theory of Epidemiological Science of the XXI Century - A. B. Belov (Эпидемиология и вакцинопрофилактика)
The academician V. D. Belyakov - one of the outstanding scientists-epidemiologists who have exerted fruitful impact on development of domestic epidemiological science and preventive medicine in general. In article the main stages of scientific activity of the scientist are considered: development of the theory of internal regulation of parasitic systems; creation of a paradigm of modern epidemiology as diagnostic and preventive discipline of medical science and practical health care, etc. Are shown possible ways of further development of the ideas of V. D. Belyakov and their introduction to scientific, student and preventive teaching.